2018
DOI: 10.1117/1.jbo.23.1.015007
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of the MOXY and PortaMon near-infrared spectroscopy muscle oximeters at rest and during exercise

Abstract: Abstract. The purpose of the study was to compare muscle oxygenation as measured by two portable, wireless near-infrared spectroscopy (NIRS) devices under resting and dynamic conditions. A recently developed low-cost NIRS device (MOXY) was compared against an established PortaMon system that makes use of the spatially resolved spectroscopy algorithm. The influence of increasing external pressure on tissue oxygen saturation index (TSI) indicated that both devices are stable between 2 and 20 mmHg. However, above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 56 publications
(71 reference statements)
4
120
1
1
Order By: Relevance
“…This myopathy is characterized by irregular myofiber morphology, cytoskeletal disruption, oxidative damage to myofibers and blood vessels, and fibrosis. 14,[24][25][26][27][28][29] It is the combination of these pathologic features of PAD that collaborates with macrovascular disease to produce the profoundly altered StO 2 profiles and severe walking limitation of claudicating patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This myopathy is characterized by irregular myofiber morphology, cytoskeletal disruption, oxidative damage to myofibers and blood vessels, and fibrosis. 14,[24][25][26][27][28][29] It is the combination of these pathologic features of PAD that collaborates with macrovascular disease to produce the profoundly altered StO 2 profiles and severe walking limitation of claudicating patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 This measure is comparable with other commercially available NIRS devices. 14,15 Measurement of calf muscle StO 2 during exercise (PAD and control cohort). NIRS monitors were placed over the bilateral gastrocnemius in all PAD and control participants ( Fig 1).…”
Section: Article Highlights Dmentioning
confidence: 99%
“…The device was placed on the vastus lateralis at ∼50% femur length from the lateral epicondyle and greater trochanter, and measured at a penetration depth of ∼2.5 cm (McManus et al . ). The NIRS was secured and protected from outside light, and the location was marked pre‐exercise to ensure minimal movement of the device during exercise.…”
Section: Methodsmentioning
confidence: 97%
“…But deoxyhemoglobin concentration also increased during SIT, suggesting that an increase in muscle O 2 extraction also occurs (Jones et al, 2015). We chose to only present SmO 2 here, since recent studies have found that the Moxy monitor provides credible and reliable SmO 2 values (McManus et al, 2018), but that total hemoglobin values had low variation during exercise and were probably not a valid indicator of blood volume (Crum et al, 2017).…”
Section: Hiit and Peripheral Demandmentioning
confidence: 99%